External Validation and Extension of the NAPLS-2 and SIPS-RC Personalized Risk Calculators in an Independent Clinical High-Risk Sample - Osborne, K. Juston (Psychiatry Res, 2019)
Early identification of individuals likely to develop psychosis is a priority for the field, resulting in the development of risk calculators that provide personalized estimates that an individual at clinical high-risk (CHR) will develop psychosis. The North American Prodrome Longitudinal Study (NAPLS) consortium and Shanghai At-Risk for Psychosis program have recently developed such calculators (NAPLS-2/SIPS-RC, respectively), but their discrimination performance has never been examined within the same sample. Moreover, validation studies of NAPLS-2 are limited in number and the SIPS-RC has not been cross-validated in a North American sample. The present research (N = 68) used the area under the receiver operating characteristic curve (AUC) to examine the accuracy of the NAPLS-2 and SIPS-RC calculators for discriminating CHR converters and non-converters, as well as extend their use by examining their ability to predict illness progression over a two-year period. For conversion, the NAPLS-2 and SIPS-RC risk calculators demonstrated moderate (AUC = .71) and fair (AUC = .65) discrimination performance, respectively. Both calculators provided moderate accuracy for discriminating illness progression over two-years (NAPLS-2 AUC = .71/ SIPS-RC AUC =. 76). We discuss implications for researchers and practitioners interested in using the NAPLS-2 and/or SIPS-RC and identify important steps for future research.